The effectiveness of realistic mathematics education to enhance elementary students' learning outcomes and motivation - Jesi Alexander Alim; Sri Retno Asih; Zetra Hainul Putra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
The implementation of mathematics can always be found in everyday life. In mathematics education, the main focus of RME is its approach, which emphasizes using real-life situations in mathematics learning. This study aims to examine the effectiveness of Realistic Mathematics Education (RME) in improving mathematics learning outcomes and motivation among fourth-grade elementary school students. This research is a quantitative study with a one-group quasi-experimental design. The study was conducted in a fourth-grade classroom involving 27 students. Data were collected through pretest and post-test questions. The data analysis used was the paired sample t-test and n-gain test. The study's results indicate a significant difference between the post-test and pretest results in students' learning outcomes and motivation before and after implementing Realistic Mathematics Education (RME). This is based on the paired sample t-test results, which show that the significance value for learning outcomes after the implementation of RME is 0.000 < 0.05, and the significance value for motivation is 0.01 < 0.05. The n-gain calculation also indicates that the effectiveness of implementing Realistic Mathematics Education (RME) falls within the moderate category. Overall, it is concluded that applying realistic mathematics education (RME) is practical for teaching and improving fourth-grade elementary school students' learning outcomes and motivation.